Cost comparison of MRSA screening and management - a decision tree analysis - Tübbicke Andrea; Hübner Claudia; Hübner Nils-Olaf; Wegner Christian; Kramer Axel; Fleßa Steffen (BMC, 2012)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) infections represent a serious challenge for health-care institutions. Rapid and precise identification of MRSA carriers can help to reduce both nosocomial transmissions and unnecessary isolations and associated costs. The practical details of MRSA screenings (who, how, when and where to screen) remain a controversial issue. Methods Aim of this study was to determine which MRSA screening and management strategy causes the lowest expected cost for a hospital. For this cost analysis a decision analytic cost model was developed, primary based on data from peer-reviewed literature. Single and multiplex sensitivity analyses of the parameters "costs per MRSA case per day", "costs for pre-emptive isolation per day", "MRSA rate of transmission not in isolation per day" and "MRSA prevalence" were conducted. Results The omission of MRSA screening was identified as the alternative with the highest risk for the hospital. Universal MRSA screening strategies are by far more cost-intensive than targeted screening approaches. Culture confirmation of positive PCR results in combination with pre-emptive isolation generates the lowest costs for a hospital. This strategy minimizes the chance of false-positive results as well as the possibility of MRSA cross transmissions and therefore contains the costs for the hospital. These results were confirmed by multiplex and single sensitivity analyses. Single sensitivity analyses have shown that the parameters "MRSA prevalence" and the "rate of MRSA of transmission per day of non-isolated patients" exert the greatest influence on the choice of the favorite screening strategy. Conclusions It was shown that universal MRSA screening strategies are far more cost-intensive than the targeted screening approaches. In addition, it was demonstrated that all targeted screening strategies produce lower costs than not performing a screening at all.